Cardiovascular Risks and Outcome in COVID-19 Positive Patients With Cardiovascular Disease Attending Primary Health Care Corporation in Qatar: A Retrospective Cohort Study - Maktoum Abdul Azeez, MBBS, MRCP, FRCP, FRCGP, MSc; Abdul Hakeem Hamza, MBBS, MRCGP; Mohamed Ali Kalathingal, MBBS, MRCGP; Sabir Abdul Karim, MBBS, MRCP, FRCP, FEACVI, FSCMR; Mohamed Shaheen Anodiyil, MBBS, MRCGP; Jazeel Abdulmajeed, MPH; Jeyaram Illiayaraja Krishnan, MSc, MPhil; Shajitha Thekke Veettil, MSc, PhD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Background: Coronavirus disease (COVID-19) patients with cardiovascular disease (CVD) are at a higher risk of morbidity and mortality. This study describes the risks and outcome in COVID-19 patients with CVD attending Primary Health Care Corporationsettings in Qatar. Objective: To report whether CVD increases the risk for hospitalization and further complications in COVID-19 patients. Methods: Retrospective cohort study. Results: A total of 10,178 CVD patients’ data who tested positive for COVID-19 were extracted from electronic medical records on the basis of inclusion criteria and analyzed during the period of February 1, 2020 to December 31, 2020 (11 months). Among the patients included in the study, 64% (n=6527) were men and 36% (n=3651) were women; 23% (n=2299) were Qataris and 77% (n=7879) were non-Qataris. Among the selected age group of greater than 25 to less than 75 years, the median age was 50.83 years. More than half of the patients had diabetes (69.6%; n=7086) followed by hypertension (68.4%; n=6965) and dyslipidemia (45.1%; n=4590). Other comorbidities were obesity (18.3%; n=1862), kidney disease (6.5%; n=659), hematologic problems (4.2%; n=425), liver disorders (1.4%; n=142), rheumatic heart disease (1.3%; n=131) and neurologic symptoms (1.3%; n=128). Multivariate analysis for factors associated with inpatient admissions in last 28 days for patients with CVD reported that patients with age greater than 70 years are 2.8 (1.86-4.18) times higher risk of hospital admission as compared with the patients 25-30 years of age. Conclusion: The pre-existing CVD with age and other comorbidities predict the risk for hospitalization and further complications in patients with COVID-19. Further studies are needed to investigate the data from primary and secondary care about the long-term cardiovascular outcomes of patients who have survived COVID-19.